Uma docência em meio ao devir-criança atravessada por processos de escrita - Silva, Luana da (2024)
In this dissertation, poetry and images are touched in thinking teaching in midst of becoming-child, setting itself up as a minor writing that is weaved alongside Roland Barthes (2015), Gilles Deleuze (2011), Gilles Deleuze e Félix Guattari (2012), Sandra Corazza (2004, 2009), Rosane Preciosa (2002) e Silvio Gallo (2003). The processes of writing intersect each other, being affected by childhoods, seeking for careful listening to the children. This way, touching and mumbling with the concepts of becomingchild, minor education and writing, gaps are created in the attempt to make fissures with the question: What can be tensioned by writing when moving a teaching crossed by becoming-child? The research adopts an essayistic methodological path, as one writes through events, through the affects that emerge when composing with fragments, poetry and images. A writing that seeks to weave together with arts, teaching and childhoods, other ways of inventing and essaying with children.